2009
DOI: 10.1097/nna.0b013e3181b9209c
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic Medical Records on Nursing Efficiency

Abstract: The authors review the literature and describe the potential impact of electronic medical records on nursing efficiency, as measured by a reduction in the amount of time nurses spend on activities that are not part of direct patient care. They also identify factors leading to success or failure in achieving electronic medical record-enabled nursing efficiency and illustrate their impact using a case study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, recent empirical studies examining the impact of specific EMR applications on nurse time have not found significant time savings (Franklin, O'Grady, Donyai, Jacklin, & Barber, 2007;Hakes & Whittington, 2008;Asaro & Boxerman, 2008). A recent case study found that EMR reduced total charting time by 50 to 73 minutes per nurse per 12hour shift; however, these time savings were not used to reduce staffing levels (Thompson, Johnston, & Spurr, 2009).…”
mentioning
confidence: 99%
“…However, recent empirical studies examining the impact of specific EMR applications on nurse time have not found significant time savings (Franklin, O'Grady, Donyai, Jacklin, & Barber, 2007;Hakes & Whittington, 2008;Asaro & Boxerman, 2008). A recent case study found that EMR reduced total charting time by 50 to 73 minutes per nurse per 12hour shift; however, these time savings were not used to reduce staffing levels (Thompson, Johnston, & Spurr, 2009).…”
mentioning
confidence: 99%
“…6 Nursing documentation can become a mechanism for improvement and innovation of nursing care in the PHC, all set in a more democratic, more patient-centered way, and for sharing information among all health professionals involved in the patient's health. 7,8 We need a willing and positive motivational environment to adopt these new tools, both in the initial phase of its implementation and in the subsequent phases to be sure to provide training and support to professionals who handle the EHR.…”
Section: Introductionmentioning
confidence: 99%
“…This is congruent with research examining time efficiency of nurses after technology implementation, which found time savings for certain nursing activities, such as searching for charts and order clarification. 5 As familiarity with the electronic system and new workflows increased, end-user efficiency improved over pre-CPOE efforts.…”
Section: Remediation Plan As Implementedmentioning
confidence: 99%